Pacu Sampan as a Cultural Tourism Attraction: A Study on Tourism Development Potential at The Taman Bunga Impian Okura Pekanbaru - Mariaty Ibrahim; Elti Martina; Etika Etika; Nurul Asyifa; Yogi Prambudi; M. Zacky Faluti (International Journal of Science and Environment (IJSE), 2025)
The research was conducted at one of Pekanbaru’s tourist attractions, Taman Bunga Impian Okura, which served as the study location and research object for tourism development. Tourism development plays a crucial role today in preventing visitor fatigue caused by repetitive offerings. Therefore, destination managers must actively explore development opportunities to encourage repeat visits and create renewed tourist experiences. Pacu Jalur, a water-based traditional rowing festival held in Kuansing Regency, is one example of a cultural tourism attraction featured on the international tourism calendar. Inspired by Pacu Jalur’s success in utilizing cultural uniqueness, Taman Bunga Impian Okura also promotes pacu sampan culture as a potential tourism attraction. In addition to functioning as a recreational paddle sport, this activity supports natural and man-made educational tourism as well as sports tourism. Taman Bunga Impian Okura features a diverse collection of ornamental flowers, numerous handmade creative products, and performances showcasing local arts, culture, and culinary traditions. Its development has contributed to economic revitalization and generated new employment opportunities for the surrounding community. Continuous innovation and diversification of attractions have helped position Taman Bunga Impian Okura as a floral tourism destination in Pekanbaru. Strategically located along the banks of the Siak River, the site offers environmental, cultural, and recreational potential capable of enhancing the visitor experience. Research findings suggest that Taman Bunga Impian Okura, with its riverfront location, is being developed as a sports-based tourism destination to strengthen visitor engagement and increase tourist interest.